Co-Pyrolysis Upgrading of High-Ash Biogas Residue with Lignocellulosic Biomass: Synergistic Kinetics, Energy Enhancement, and EBC-Compliant Biochar Production - Chung-Liang Chang; Minh Phu Nguyen; Hong-Kai Li; Chin-Chao Chen; Chyi-How Lay; Chiu-Yue Lin (BioEnergy Research, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

The comparison between multiple linear regression and random forest model in predicting environmental noise and its frequency components level in Hong Kong using a land-use regression approach - Chui Hei Wong; Zhiyuan Li; Steve Hung Lam Yim; Ta-Yuan Chang; Chung Ling Man; Chin Ho Cheng; Timothy Chi-yui Kwok; Kin Fai Ho (Environmental Research, 2025)

Streptococcus atopica sp. nov., Isolated from the Feces of a Toddler with Atopic Dermatitis - Chin-Kan Chan; Hui-Shan Wu; Li-Jyun Tsai; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yi-Sheng Chen (Current Microbiology, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Safety and antioxidant assessments of BLR-E50, 50% ethanolic extract from red beans co-fermented by Bacillus subtilis and Lactobacillus bulgaricus - Su-Tze Chou; Yi-Hua Chen; Yi-Hung Chen; Yu‐Chen Tsai; Yun-Chin Chung; Ju-Pi Li (Food and Chemical Toxicology, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Application of Cytochrome P450 Monooxygenases in Plant for Rapid Detection of 2,3,7,8 Tetrachlorodibenzodioxin in the Contaminated Sites - Ho Man Leung; Ka Chun Sung; Lai Yan Woo; Wing Yin Mo; Kwai Chung Cheung; Chi Kin Au; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Assessment of Spatial Variability of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Soils and Fungal Disease Status of Trees Grown in Hong Kong Areas - Ka Chun Sung; Ho Man Leung; Chi Fung Lee; Tohidi Fatemeh; Wing Yin Mo; Lai Yan Woo; Kwai Chung Cheung; Uchenna Ogbonnaya; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Physicochemical characteristics of grease-trap wastewater with different potential mechanisms of FOG solid formation, separation, and accumulation inside grease traps - Ling Ying Tang; Ngie Hing Wong; Thion Am Chieng; Alex Kwong Jun Kiu; Chung Siung Choo; Yali Li; Chin Ping Tan; Abu Zahrim Yaser; Deni Shidqi Khaerudini; Gui Hua Chen; Jaka Sunarso (Water Research, 2024)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

Cyclodextrin-modified layered double hydroxide thin-film nanocomposite desalination membrane for boron removal - Liang Ying Ee; Qipeng Zhao; Jie Gao; Chit Kai Lim; Kai Xue; Sze Yuet Chin; Sam Fong Yau Li; Tai-Shung Chung; Shing Bor Chen (Chemical Engineering Journal, 2023)

Corrigendum to “Effectiveness and appropriateness of core areas in an integrated protected area: A case study of Ecological Protected Areas in Yangmingshan National Park, Taiwan” [Environ. Sci. Policy 145 (2023) 175–187] - Li-Wen Chung; Chin-Liang Chao; Min-Chun Liao; Chieh-Wen Kao; Dau-Jye Lu (Environmental Science & Policy, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Hydrogen sulfide (H2S) conversion to hydrogen (H2) and value-added chemicals: Progress, challenges and outlook - Yi Herng Chan; Adrian Chun Minh Loy; Kin Wai Cheah; Slyvester Yew Wang Chai; Lock Hei Ngu; Bing Shen How; Claudia Li; Serene Sow Mun Lock; Mee Kee Wong; Chung Loong Yiin; Bridgid Lai Fui Chin; Zhe Phak Chan; et al. (Chemical Engineering Journal, 2023)

Altered glucose metabolism and its association with carbonic anhydrase 8 in Machado-Joseph Disease - Guan-Yu Lin; Chung-Yung Ma; Li-Chung Kuo; Benjamin Y. Hsieh; Hanbing Wang; Chin-San Liu; Mingli Hsieh (Metabolic Brain Disease, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

An assessment of heavy metal contamination in the marine soil/sediment of Coles Bay Area, Svalbard, and Greater Bay Area, China: a baseline survey from a rapidly developing bay - Ho Man Leung; Kwai Chung Cheung; Chi Kin Au; Ken Kin Lam Yung; Wai Chin Li (Environmental Science and Pollution Research, 2021)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Behavioural toxicity studies of Cyclope neritea and Nassarius mutabilis exposed to polycyclic aromatic hydrocarbons - Ho Man Leung; Patrick Ying Kit Yue; Stephen Cho Wing Sze; Chi Kin Au; Kwai Chung Cheung; Ka Loi Chan; Ho Yiu Lok; Wai Chin Li; Ken Kin Lam Yung (Environmental Science and Pollution Research, 2020)

The potential of Mikania micrantha (Chinese creeper) to hyperaccumulate heavy metals in soil contaminated by electronic waste - Ho Man Leung; Patrick Ying Kit Yue; Stephen Cho Wing Sze; Chi Kin Au; Kwai Chung Cheung; Ka Loi Chan; Kin Lam Ken Yung; Wai Chin Li (Environmental Science and Pollution Research, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Erratum to: Hypoxia Augments Increased HIF-1a and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Syun Hu; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2018)

Inter-comparison of Chemical Composition and Originality of Atmospheric PM10 at Coastal Regions and Offshore Islands in the Subtropical East Asia - Chien-Chin Liao; Chung-Shin Yuan; Tsung-Chang Li; Chang-Tang Chang; Chuan Tong (Aerosol Science and Engineering, 2018)

Hypoxia Augments Increased HIF-1α and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2016)

ZAK induces cardiomyocyte hypertrophy and brain natriuretic peptide expression via p38/JNK signaling and GATA4/c-Jun transcriptional factor activation - You-Liang Hsieh; Ying-Lan Tsai; Marthandam Asokan Shibu; Chia-chi Su; Li-Chin Chung; Peiying Pai; Chia-Hua Kuo; Yu-Lan Yeh; Vijaya Padma Viswanadha; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

Gelsolin (GSN) induces cardiomyocyte hypertrophy and BNP expression via p38 signaling and GATA-4 transcriptional factor activation - Wei-Syun Hu; Tsung-Jung Ho; Peiying Pai; Li-Chin Chung; Chia-Hua Kuo; Sheng-Huang Chang; Fuu-Jen Tsai; Chang-Hai Tsai; Yu-Chi Jie; Ying-Ming Liou; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2014)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings - Shin-Lon Ho; Li-Fen Huang; Chung-An Lu; Siou-Luan He; Chun-Chin Wang; Sheng-Ping Yu; Jychian Chen; Su-May Yu (Plant Molecular Biology, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Evaluation of the bioactivities of extracts of endophytes isolated from Taiwanese herbal plants - Pei-Wen Hsieh; Li-Chi Hsu; Chern-Hsiung Lai; Chin-Chung Wu; Tsong-Long Hwang; Yin-Ku Lin; Yang-Chang Wu (World Journal of Microbiology and Biotechnology, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Preparation and characterization of water-soluble chitosan produced by Maillard reaction - Ying Chien CHUNG; Cheng Fang TSAI; Chin Fung LI (Fisheries Science, 2006)

Methanosarcina mazei Strain O1M9704, Methanogen with Novel Tubule Isolated from Estuarine Environment - Mei-Chin Lai; Chin-Ming Shu; Sheng-Chung Chen; Li-Jane Lai; Ming-Shing Chiou; Jack Jay Hua (Current Microbiology, 2000)